2009
DOI: 10.1021/ja809697p
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Diamine Derivatives via Sequential Palladium and Rhodium Catalysis

Abstract: The use of a bifunctional nitrogen nucleophile and an allyl carbonate starting material in successive enantioselective palladium- and diastereoselective rhodium-catalyzed reactions enables the rapid assembly of unique amino aziridine products. Further elaboration of these materials affords complex, stereodefined polyamine architectures, thus demonstrating the power of these combined methods for simplifying asymmetric C−N bond construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 19 publications
2
41
0
1
Order By: Relevance
“…Despite its usefulness, the success of this type of reaction is limited. [46][47][48][49][50] Although no reaction occurred when 2-phenylcyclohexenyl acetate was used as the substrate, allylic amination of 2-phenylcyclohexenyl carbonate 48 with benzylamine proceeded smoothly in acetonitrile, affording the corresponding product 49a in 93% yield and 93% ee (Chart 15). Chart …”
Section: Chart 11 Enantioselective Construction Of Quaternary Centermentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its usefulness, the success of this type of reaction is limited. [46][47][48][49][50] Although no reaction occurred when 2-phenylcyclohexenyl acetate was used as the substrate, allylic amination of 2-phenylcyclohexenyl carbonate 48 with benzylamine proceeded smoothly in acetonitrile, affording the corresponding product 49a in 93% yield and 93% ee (Chart 15). Chart …”
Section: Chart 11 Enantioselective Construction Of Quaternary Centermentioning
confidence: 99%
“…51) Although this type of transformation using oxygen nucleophiles has been investigated in detail by Trost et al, [52][53][54] there are limited investigations using nitrogen nucleophiles. 47,50) This background led us to examine the asymmetric allylic amination of 2-methoxycarbonyl 2-cyclohexenyl carbonate 51 with benzylamine using our catalyst system (Chart 17). Chart …”
Section: Asymmetric Allylic Alkylation Of Cyclic Substratementioning
confidence: 99%
“…Although this type of transformation using oxygen nucleophiles has been investigated in detail by Trost et al 154e156 there are limited applications of nitrogen nucleophiles. 103,106 This background led us to examine asymmetric allylic amination of a 2-methoxycarbonyl 2-cyclohexenyl alcohol derivative 65 with benzylamine using our catalyst system (Table 10). The effect of the ligand structure revealed that the introduction of electron- Trace d a Pd (5 mol %) catalyst and 10 mol % of (S,R P )-1a were used.…”
Section: Enantioselective Synthesis Of Aza-moritaebaylisehillman Reacmentioning
confidence: 99%
“…1 Our laboratories have recently reported that two catalytic processes, Pd π-allyl coupling and Rh-catalyzed alkene aziridination, may be used in sequence to generate a previously unknown class of strained heterobicyclic products. 2 While the potential to synthesize differentially-substituted 1,2- and 1,3- diamines 3,4,5,6 from these unique oxathiadiazinane derivatives was evident, little was known about the factors that govern their stability and reactivity. Herein, we detail new protocols to prepare highly substituted forms of these heterocycles, and highlight for the first time the unusual stability and utility of Troc-protected oxathiadiazinanes for 1,2-diamine synthesis (Figure 1).…”
mentioning
confidence: 99%